1998
DOI: 10.1046/j.1432-1327.1998.2581032.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA synthesis exhibited by the reverse transcriptase of mouse mammary tumor virus : Processivity and fidelity of misinsertion and mispair extension

Abstract: We have recently expressed in bacteria an enzymatically active reverse transcriptase (RT) of mouse mammary tumor virus (MMTV), a mammalian retrovirus with a typical B-type morphology [Taube, R., Loya, S., Avidan, O., Perach, M. & Hizi, A. (1998) Biochemical J. 329, 579Ϫ587]. The purified recombinant protein was shown to possess the catalytic activities characteristic of retroviral reverse transcriptases. In the present study, we have analyzed two basic parameters characteristic of the DNA polymerase activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 35 publications
(39 reference statements)
3
19
1
Order By: Relevance
“…A very similar bias was recently reported on SRAS, although to a lower extent with A > G and T > C substitutions making about 60% of all mutations observed (Eckerle et al, 2010). This bias was never reported for in vitro activity of AMV reverse transcriptase despite extensive misincorporation survey (Operario et al, 2005;Skinner and Eperon, 1986;Taube et al, 1998). This strong mutational bias is suggestive of the activity of a family of host cell proteins known as Adenosine Deaminases that Act on RNA or ADAR (Bass, 2002).…”
Section: Mutation Previously Reportedsupporting
confidence: 79%
“…A very similar bias was recently reported on SRAS, although to a lower extent with A > G and T > C substitutions making about 60% of all mutations observed (Eckerle et al, 2010). This bias was never reported for in vitro activity of AMV reverse transcriptase despite extensive misincorporation survey (Operario et al, 2005;Skinner and Eperon, 1986;Taube et al, 1998). This strong mutational bias is suggestive of the activity of a family of host cell proteins known as Adenosine Deaminases that Act on RNA or ADAR (Bass, 2002).…”
Section: Mutation Previously Reportedsupporting
confidence: 79%
“…All our previous studies with a variety of retroviral RTs have shown that the parameters for fidelity of DNA synthesis in vitro (i.e. 3′ end misinsertion and the extension of the performed 3′ end mispaired primers) depend primarily on the sequences of nucleic acids copied, rather than whether DNA or RNA templates were copied [16,18,20,23]. Subsequently, in the present study we have analysed DNA templates as representing both DNA and RNA substrates.…”
Section: Resultsmentioning
confidence: 98%
“…the amount of total 32 P‐labelled primer extended per minute in the conditions used. The V max and K m values were calculated from the double‐reciprocal linear plots of velocity vs. dNTP concentrations [16,18].…”
Section: Methodsmentioning
confidence: 99%
“…Bovine leukemia virus (BLV) RT showed higher misinsertion fidelity than HIV-1 RT but lower than that of MLV RT, although the patterns of mispair elongation by the BLV enzyme suggested that its fidelity was similar to that reported for HIV-1 RT [105]. The MMTV RT was about 2- to 4-fold more error prone than AMV RT in misinsertion assays and showed a higher ability to extend mismatched template-primers [106]. On the other hand, misinsertion and mispair extension ratios obtained with RTs from porcine endogenous retrovirus were roughly similar to those obtained with MLV RT [107].…”
Section: Assessing Fidelity Of Dna Synthesis Using Nucleotide Incorpomentioning
confidence: 99%